A non‐intrusive Smart metering system: Analytics and simulation of power consumption. (16th April 2019) - Fecil'ak, Peter; Pekár, Adrián; Ádám, Norbert; Baláž, Anton; Chovancová, Eva
Summary: This contribution deals with the design and experimental implementation of a Smart Metering Architecture which supports different transport technologies, ie, Ethernet, WiFi, and LoRa. Appropriate methods for measuring electrical quantities have been analysed, which resulted in a couple of prototypes. The contribution describes the design and implementation of two versions of measuring devices, which were used for the purpose of experimental implementation. The test results have shown that the latest version of the measuring device based on a Teridian on‐chip metering system is more precise in terms of measuring accuracy. The presented paper shares the results of the data analytics based on NIALM algorithm and power profile disaggregation in a test environment. Simulation tool, which helps us to predict the power consumption of the defined location based on realistic behaviour and in combination with realistic data from the developed Smart metering prototypes, has been also documented in this research paper.